Odkrivanje kolonizacije nosečnic z bakterijo Streptococcus agalactiae v severnoprimorski regiji - Fišer, Jerneja (Zdravniški vestnik, 2001)
Background. Streptococcus agalactiae (GBS) is a leading cause of neonatal sepsis and meningitis. Newborns are colonized with GBS at the time of delivery. Since vertical transmission from colonized mother to infant is required for the development of disease, the aim of our study, Detection of Colonization of Pregnant Women with Streptococcus agalactiae in the Severnoprimorska Region was to determine the rate of vaginal and rectal GBS colonization of pregnant women. Methods. Methods of GBS detection were derivedfrom the 1996 CDC (Centers for Disease Control and Prevention) guidelines (1), recommending taking the vaginal and rectal smears of pregnant women between 3th and 37th weeks of pregnancy and use of selective broth. Our one-year study (from the beginning of April 1999 to the end of April 2000) wasat first intended to include only pregnant women between 35th and 37th weeks of pregnancy to whom two smears were taken, but gynaecologists, althoughthey were given exact instructions, often took smears before 35th or after 37th week of pregnancy, or indicated no week of pregnancy; moreover, to 30 pregnant women they only took one smear. We therefore decided to include these pregnant women in our study, too. After taking the smears the gynaecologists put the swabs in a selective broth medium with antibiotics and immediately sent them to the microbiology laboratory for GBS identification. Results. 830 pregnant women were examined for GBS; in 800 cases 2 smears were taken, in 30 cases only the vaginal smear. 567 women were examined between 35th and 37th weeks of pregnancy, 22,3% were colonized with GBS; 201 women were examined between 30th and 34th week, 25.8% were colonized with GBS. Of all 830 pregnant women examined 192 women (more than 23%) were found colonizedwith GBS; 12% had GBS in both vagina and rectum, 7.3% only in the vagina and 3.7% only in the rectum. (Abstract truncated at 2000 characters)
Keywords: diagnostika; human pregnancy; infekcije; Isolation and purification; Microbiology; nosečnice; Nosečnost; Pregnancy; Rectum; Rektum; Streptococcus agalactiae; Streptokokus agalakcije; Vaginal smears; Vaginalni razmazi